QSPR Analysis of Novel Topological Index Based on Proximity Degree - Kumar, Deepasree S.; Ranjini, P. S.; Haque, Md. Samiul; Lokesha, V. (Communications in Mathematics and Applications, 2024)
In this article, we define a \(k\)-proximity degree and based on this distance degree, we introduce a novel topological index named Proximity Index \((\PI_k)\). By considering octane and heptane isomers, we have studied QSPR regression analysis to predict the physio-chemical properties and chemical applicability of the index.
Keywords: Proximity degree; QSPR analysis; Octane isomers; Heptane isomers